Ferromagnetic cluster glass behavior and large magnetocaloric effect in Ho2PtSi3. (December 2017) - Li, D.X.; Homma, Y.; Nakamura, A.; Shimizu, Y.; Honda, F.; Yamamura, T.; Aoki, D.
Abstract: Magnetic properties and magnetocaloric effect of Ho2 PtSi3, a new ternary intermetallic compound with the orthorhombic Ba2 LiSi3 -type structure, are studied by dc magnetization, ac susceptibility, magnetic relaxation, specific heat, and magnetic memory effect measurements. The experimental results indicate that this system undergoes a magnetic phase transition from a paramagnetic state to a ferromagnetic cluster state at a temperature T C ~ 6.5 K followed by a cluster glass transition at T f ~ 5.8 K. The typical cluster glass features observed below T f for Ho2 PtSi3 include (1) broad peak in specific heat curve, (2) frequency dependent cusp in ac susceptibility curve, (3) evident irreversible magnetism, (4) long-time magnetic relaxation behavior, and (5) zero-field-cooling magnetic memory effect. On the other hand, the large values of magnetic entropy change, relative cooling power and adiabatic temperature change are estimated near T C under a field change. These results suggest that Ho2 PtSi3 can be classified as a huge ferromagnetic cluster glass system with large magnetocaloric effect. Highlights: Ho2 PtSi3 is confirmed to be a new nonmagnetic atom disorder compound with Ba2 LiSi3 -type structure. Large ferromagnetic clusters are found to form in Ho2 PtSi3 at T C ~ 6.5 K. Below T f ~ 5.8 K, Ho2 PtSi3 shows the evident cluster glass behaviors. Large values of − Δ S m max = 24.2 J kg −1  K −1, RCP = 414 J kg −1 and Δ T a d max = 9.0 K are estimated near T C for Δ H = 5 T. Ho2 PtSi3 can be considered as a ferromagnetic cluster glass system with large magnetocaloric effect.